2002
DOI: 10.1063/1.1499744
|View full text |Cite
|
Sign up to set email alerts
|

Output enhancement of spin-valve giant magnetoresistance in current-perpendicular-to-plane geometry

Abstract: In this work, we present a suitable material for metal-based spin-valve in current-perpendicular-to-plane (CPP) geometry. The AΔR (A is the element size and ΔR is the change in resistance) was investigated for three kinds of free and pinned layers material, that is, Co90Fe10, Fe50Co50, and Fe50Co50 with half-atomic Cu layers. When the free and pinned layers are 5 nm, AΔR is 1.0 mΩ μm2, 1.6 mΩ μm2, and 2.9 mΩ μm2, respectively. Moreover, the dual-type spin valve having Fe50Co50 with half-atomic Cu layers achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 15 publications
0
40
1
Order By: Relevance
“…Consequently, the optimization of GMR is an important challenge for future CPP sensors. It has already been demonstrated that appropriate laminations in the magnetic layers can significantly increase RA [32]. However, further improvements are still required to increase the effective signal in CPP-GMR sensors.…”
Section: Cpp-gmr Sensors and Headsmentioning
confidence: 96%
“…Consequently, the optimization of GMR is an important challenge for future CPP sensors. It has already been demonstrated that appropriate laminations in the magnetic layers can significantly increase RA [32]. However, further improvements are still required to increase the effective signal in CPP-GMR sensors.…”
Section: Cpp-gmr Sensors and Headsmentioning
confidence: 96%
“…100 mm and r 10 mm, R c will be comparable to R s . Since this R c is the same for AR AP and AR P , it will not affect ADR, but will reduce the CPP-MR. Because the "ln" term varies weakly with (1/r) / (1/ ffiffiffi A p ), for a small enough range of 1/A, a plot of the measured AR m versus 1/A might approximate a straight line with slope AR P or AR AP [109]. 2.…”
Section: Appendix Supplementary Note #1: Contact Resistances and Nonumentioning
confidence: 98%
“…In recent years the CPP mode of conduction is increasingly preferred in spin valves as it can potentially achieve a higher GMR ratio [4][5][6][7][8][9]. The GMR ratio is defined as the fractional change in resistance when the magnetization alignment in the spin-valve multilayer switches from a parallel to an antiparallel alignment.…”
Section: Introductionmentioning
confidence: 99%